2017
DOI: 10.1158/1078-0432.ccr-16-1147
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Lengthening of Telomeres in Primary Pancreatic Neuroendocrine Tumors Is Associated with Aggressive Clinical Behavior and Poor Survival

Abstract: Purpose Alternative lengthening of telomeres (ALT), a telomerase-independent telomere maintenance mechanism, is strongly associated with ATRX and DAXX alterations and occurs frequently in pancreatic neuroendocrine tumors (PanNETs). Experimental design In a Korean cohort of 269 surgically resected primary PanNETs and 19 sporadic microadenomas, ALT status and nuclear ATRX and DAXX protein expression were assessed and compared with clinicopathologic factors. Results In PanNETs, ALT or loss of ATRX/DAXX nuclea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
127
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 118 publications
(139 citation statements)
references
References 30 publications
12
127
0
Order By: Relevance
“…Therefore, cases were visually assessed and classified as ALT‐positive if ultrabright nuclear foci of telomere FISH signals were present in the cancer cells. The total intensities of individual ALT‐associated, ultrabright nuclear foci have been previously measured as >10‐fold higher than the mean integrated signal intensities for individual nonneoplastic cells in the same cases …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, cases were visually assessed and classified as ALT‐positive if ultrabright nuclear foci of telomere FISH signals were present in the cancer cells. The total intensities of individual ALT‐associated, ultrabright nuclear foci have been previously measured as >10‐fold higher than the mean integrated signal intensities for individual nonneoplastic cells in the same cases …”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated that, compared with ALT‐negative and ATRX/DAXX‐intact tumors, ALT‐positive and ATRX/DAXX‐negative primary PanNETs tend to be larger in size, have a higher World Health Organization grade, and are more likely to develop lymph node and distant metastases . ALT is a critical mechanism of carcinogenesis in PanNETs; and, as such, our ability to evaluate the status of these biomarkers will aid in the design of future clinical trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available evidence suggests that mutations of MEN1 play a key role in tumor initiation, whereas late alterations of DAXX/ATRX seem to be implicated in tumor progression . Loss of DAXX/ATRX expression has been associated with activation of the alternative lengthening of telomeres (ALT) pathway and chromosomal instability, and poor outcomes have been reported for patients with ALT‐positive tumors . Three distinct molecular subtypes of pNETs recently have been identified: 1) the islet/insulinoma tumor subtype is characterized by low grade and limited metastatic potential; 2) the metastasis‐like primary subtype is characterized by high proliferative activity and aggressive behavior; and 3) the MEN1‐like/intermediate subtype shows moderate metastatic potential …”
Section: Molecular Geneticsmentioning
confidence: 99%
“…Several markers have the potential to identify high and low risk subgroups. PanNET tumorigenesis is commonly driven by mutations in the tumor suppressor genes MEN1 , ATRX , or DAXX , of which the latter two are associated with the alternative lengthening of telomeres phenotype (ALT) and correlate with worse prognosis and liver metastases . Protein loss, detected by immunohistochemistry (IHC), can be used as a surrogate for somatic inactivating mutations in ATRX and DAXX .…”
Section: Introductionmentioning
confidence: 99%